2023
DOI: 10.3390/jrfm16080361
|View full text |Cite
|
Sign up to set email alerts
|

Risk and Bankruptcy Research: Mapping the State of the Art

Abstract: This article presents a bibliometric study on different types of risk and bankruptcy, aiming to contribute to academic knowledge in this area. We used the bibliometrix tools in R and VOSviewer, following the main laws of bibliometrics (Bradford’s law, Lotka’s law, and Zipf’s law). We analyzed 7163 relevant academic publications retrieved from the WOS database between 1995 and 2023. The characterization of the literature identified trends, importance, and scientific relevance of works, journals, and authors. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 72 publications
(107 reference statements)
0
3
0
Order By: Relevance
“…Applying Zipf's Law to analyze word frequency can benefit indexing in a particular domain. Similar to the works of Almeida (2023) and Almeida and Vieira (2023), we evaluate if the three vital bibliometric laws apply to the study's data.…”
Section: Keyword Frequency Via Zipf's Law Lensmentioning
confidence: 99%
“…Applying Zipf's Law to analyze word frequency can benefit indexing in a particular domain. Similar to the works of Almeida (2023) and Almeida and Vieira (2023), we evaluate if the three vital bibliometric laws apply to the study's data.…”
Section: Keyword Frequency Via Zipf's Law Lensmentioning
confidence: 99%
“…For Tavares et al (2021) and Santos et al (2022), image risks are linked to the company's reputation, which it transfers abroad. On the other hand, these authors consider Risks 2024, 12, 91 2 of 20 that financial risks are associated with the economic and financial capacity of companies and the way they carry out their business, an idea corroborated by Almeida (2023). Financial risks are distinguished between short-term and medium-and long-term risks.…”
Section: Introductionmentioning
confidence: 99%
“…The data was analyzed using many programs (RStudio, VOSviewer, and Excel), and the most active actors in terms of nations, institutions, sources, documents, and authors were shown. (Almeida, 2023) To identify academic domains that have made substantial research contributions, we summarized 711 bibliometric publications on AI & its sub-sets and BDA that were published in various fields. From the Scopus Q1 and Q2 journal databases, we selected bibliometric review articles from publications between 2012 and 2022.…”
mentioning
confidence: 99%